PENGARUH TERAPI MUSIK DENGAN BRAINWAVE TERHADAP PENURUNAN INSOMNIA PADA MAHASISWA TINGKAT AKHIR DI STIKES KUSUMA HUSADA SURAKARTA - Adi Buyu Prakoso; Wahyu Rima Agustin; Maria Wisnu Kanita (Universitas Kusuma Husada Surakarta, 2020)
Sleep is a basic human need. Every one may experience sleep disorder. Insomnia is a condition in which one encounters difficulty in sleeping especially at night. A variety of managements to deal with insomnia are very required b students considering its impacts on their productivity. Brainwave is a music created by adjusting its frequency in such a way that the brain is affected when listening to it periodically. The objective of this research is to investigate the effect brainwave music therapy on insomnia reduction of final-year students. This research used the quasi experimental research method with one-group pretest-posttest design. Consecutive sampling was used to determine its samples. They consisted of 18 respondents. The data of the research were analyzed by using the Wilcoxon’s Test. The result of Wilcoxon’s Test shows that the p-value was 0.000 which was less than 0.05, meaning that the brainwave music therapy could reduce insomnia of the final-year students of Kusuma Husada College of Health Sciences of Surakarta. Thus, the brainwave music therapy had an effect on insomnia following the therapy. The result of this research is expected to be used as a non-pharmacological intervention to deal with insomnia.